Analysis of dynamic characteristics of marine deaerator - Guoqing Zeng; Wenhao Wu; Guobing Chen; Jun Li; Xuefeng Wang (Energy Reports, 2022)
According to the operating characteristics of deaeration equipment in marine steam power system, this paper uses the multi-domain physical modeling language-Modelica and Mworks simulation platform to establish a deaerator simulation model based on the working principle of the deaerator and the equations of energy and mass conservation. Analyze the dynamic response characteristics of the deaerator under variable operating conditions of the power system. The results show that under 100% operating conditions, the static simulation error of the model is within 2%; and under the variable operating conditions, the dynamic response of the deaerator is consistent with the actual operating conditions, which can provide a reference for the optimization of the marine steam power system.